A review of train aerodynamics Part 1 – Fundamentals. (March 2014) - Baker, C. J.
Abstract: This paper is the first of a two-part review of train aerodynamics. After an initial introduction and broad survey of train aerodynamic issues, and a discussion of measurement, modelling and computational techniques, the nature of the flow around trains is considered – in the open air, with and without crosswinds, and in confined geometrical situations and tunnels. The flow in different regions around the train is described and the main flow features outlined. Part 2 of the paper will then consider a number of issues that are of concern in the design and operation of modern trains based on this description of the overall flow field.